2015
DOI: 10.1017/s1368980015001317
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body image dissatisfaction and BMI change in school-age children

Abstract: Objective: Parental body image dissatisfaction (BID) is associated with children's weight in cross-sectional studies; however, it is unknown whether BID predicts development of adiposity. The objective of the present study was to investigate the associations between maternal dissatisfaction with her or her child's body and children's BMI trajectories. Design: Longitudinal study. Maternal dissatisfaction (BID) with her and her child's body was calculated based on ratings of Stunkard scales obtained at recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…Table 1 presents a detailed description of the main studies found in this review. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 The following were highlighted: authors; country; year of publication; method employed; characteristics of the sample; size of the assessed body image; and evaluation instrument used. It should be noted that a sample size varied from 25 to 11,466 children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents a detailed description of the main studies found in this review. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 The following were highlighted: authors; country; year of publication; method employed; characteristics of the sample; size of the assessed body image; and evaluation instrument used. It should be noted that a sample size varied from 25 to 11,466 children.…”
Section: Resultsmentioning
confidence: 99%
“…However, one of the main limitations pointed out by the surveys was the use of invalidated collection instruments for the populations of interest. 13 , 14 , 16 , 19 , 20 , 21 , 24 , 31 , 33 , 36 Other limitations were also reported. For example, the cross-sectional design, 13 , 15 , 19 , 24 , 27 , 29 , 30 , 32 , 34 , 35 , 38 , 39 , 40 , 42 , 44 because it precludes causal inferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family is known to hold meaningful influence over their children’s eating habits, and mothers play an important role on educating and selecting foods for their offspring [ 1 6 ]. Therefore, the way mothers perceive their child's body and the presence of maternal dissatisfaction with their child's body may affect their attitudes and practices related to the child's dietary intake [ 1 , 4 , 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that maternal dissatisfaction is associated with the child's sex, age, and nutritional status [ 11 13 ]. Additionally, maternal characteristics and the way the mother perceives her own body may also influence the way she perceives her child's body [ 4 , 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%